Iron-catalyzed ortho C−H arylation and methylation of pivalophenone N−H imines - Xu, Wengang (2020)
Iron‐catalyzed ortho C−H arylation and methylation reactions of pivalophenone N−H imines are reported. The pivaloyl N−H imine proved an excellent directing group for the arylation with diarylzinc reagents in the presence of an iron‐diphosphine catalyst and 2,3‐dichlorobutane at room temperature. A similar catalytic system also allowed methylation with Me3Al at 70 °C. The pivaloyl imine of the product could be readily converted to a cyano group, thus allowing convenient preparation of ortho‐functionalized benzonitriles.